Electrical characterization and modeling of pulse-based forming techniques in RRAM arrays. (January 2016) - Grossi, Alessandro; Zambelli, Cristian; Olivo, Piero; Miranda, Enrique; Stikanov, Valeriy; Walczyk, Christian; Wenger, Christian
Highlights: We compare different pulse-based forming techniques on 4 kbits RRAM arrays. We performed post-forming modeling during Reset operation. An Incremental Form and Verify technique ( IFV ) shown the best results. This technique narrows the read current distribution, reducing the switching voltage. This allows reducing cell-to-cell variability, switching time and energy. Abstract: The forming process, which corresponds to the activation of the switching filament in Resistive Random Access Memory (RRAM) arrays, has a strong impact on the cells' performances. In this paper we characterize and compare different pulse forming techniques in terms of forming time, yield and cell-to-cell variability on 4 kbits RRAM arrays. Moreover, post-forming modeling during Reset operation of correctly working and over formed cells has been performed. An incremental form and verify technique, based on a sequence of trapezoidal waveforms with increasing voltages followed by a verify operation that terminates when the expected switching behavior has been achieved, showed the best results. This procedure narrows the post-forming current distribution whereas reducing the Reset switching voltage and the operative current. These advantages materialize in a better control of the cell-to-cell variability and in an overall time and energy saving at the system level.